2019
DOI: 10.3390/f10020096
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiological Responses of Carpinus turczaninowii L. to Various Salinity Treatments

Abstract: Carpinus turczaninowii L., commonly known as hornbeam, has significant economic and ornamental importance and is largely distributed in the northern hemisphere, including parts of China and Korea, with high adaptation to harsh conditions in very unfertile soils. In this study, the ecophysiological responses of C. turczaninowii seedlings to various salinity stress treatments (NaCl: 0, 17, 34, 51, 68, and 85 mM) were studied for 42 days by determining stress-induced changes in growth parameters and biochemical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…Deficient levels were not found in any of the species at any locations tested (Dauer et al 2007;De Vries et al 2000;Dirr 1976;Kopinga and Van den Burg 1995;Mellert and Göttlein 2012;Van den Burg 1974). Similarly, the ranges of the N/P, N/K, N/Mg and N/Ca ratios in the leaves of all the tree species and locations were consistent with those in previously published literature (Flückiger and Braun 2003;Zhou et al 2019).…”
Section: Sensitive Intermediate Tolerantsupporting
confidence: 90%
See 2 more Smart Citations
“…Deficient levels were not found in any of the species at any locations tested (Dauer et al 2007;De Vries et al 2000;Dirr 1976;Kopinga and Van den Burg 1995;Mellert and Göttlein 2012;Van den Burg 1974). Similarly, the ranges of the N/P, N/K, N/Mg and N/Ca ratios in the leaves of all the tree species and locations were consistent with those in previously published literature (Flückiger and Braun 2003;Zhou et al 2019).…”
Section: Sensitive Intermediate Tolerantsupporting
confidence: 90%
“…Only after exceeding the critical level in the shoots are the ions transported in larger quantities to the leaves. Zhou et al (2019) found a higher content of Na in the roots as well as Cl mostly accumulated in leaves, suggesting a defense mechanism for Na toxicity through the compartmentalization of this element in the roots. It is possible that such a situation occurred in T. xeuchlora and G. biloba near the street in Warsaw.…”
Section: Sensitive Intermediate Tolerantmentioning
confidence: 85%
See 1 more Smart Citation
“…Salinity stress affected the values of all the examined parameters, both morphological and physiological, and caused the inhibition of plant growth, the degradation of photosynthetic capacity and stomatal behavior, a decrease in the photosynthetic pigments contents and relative water content, an increase in the Malondialdehyde (MDA) content and relative electrolytic conductivity, and the accumulation of Na + and Cl − content. The presence of relatively high concentrations of organic osmolytes, the activation of antioxidant enzymes, and the ionic transport capacity from the root to shoots may represent a constitutive mechanism of defense against stress Zhou et al [50].…”
Section: Seedsmentioning
confidence: 99%
“…Hornbeam (Carpinus turczaninowii) is known for its beautiful autumn colors and fine-textured wood. Zhou et al [15,17] systematically tested the performance of this tree species as well as its European counterpart Carpinus betulus under moderate salt stress (up to 85 mM). They found that antioxidant systems of the European species collapsed after about 1 month and that of the Asian species after about 2 months in the presence of low salinity levels (30 to 50 mM).…”
Section: Salinity and Combined Stresses: From Soil Amendment To Redoxmentioning
confidence: 99%